Lär vi oss av historien? En kvalitativ studie som undersöker två perspektiv av hållbar utveckling i relation till gruvbrytning i Kiruna - Thomsen, Hanna (2023)
To meet the contemporary demands of sustainable development, enterprises aim to undergo a green transition in order to handle the threats of climate change. Through the lens of postcolonial theories questioning the knowledge apprised from western societies, a new light can be shed on alternative approaches to global conventions such as Agenda 2030. Incorporating indigenous knowledge can be such an alternative path for the agendas fulfillment. This bachelor’s thesis aims at taking on this subject in a context of the mining industry in the northern areas of Sweden, highlighting two views on sustainability. One coming from indigenous Sami, more specifically Sametinget and the other from the mining enterprise LKAB. A qualitative text analysis can contribute to a better understanding of sustainability concerning the case with LKAB:s recent findings of rare earth metals in Kiruna, Sweden. The results show that the mining company LKAB and the Sami articulate sustainable development differently, whereas there is a conflict of interest in the case of the mining process, and thereby also a conflict in the interpretation of the concept. Conclusions can be drawn that postcolonial structures leave an imprint on today's processes, whereas the dominant, western agenda is prioritized and alternative strategies are not given enough space in the shaping of global agendas.